Net-zero, resilience, and agile closed-loop supply chain network design considering robustness and renewable energy - Lotfi, Reza; Khanbaba, Amirhossein; Ali, Sadia Samar; Afshar, Mohamad; Mehrjardi, Mojtaba Sadreddini; Omidi, Salman (Environmental science and pollution research international, 2025)
The Net-zero, Resilience, and Agile Closed-Loop Supply Chain Network (NZRACLSCND) concept integrates net-zero, resiliency, and agility in a circular economy. Regarding net-zero, this research embeds renewable energy like solar energy and hybrid trucks to supply energy for facilities and transportation of goods and products between components. Applying redundancy, multi-source, and flexible capacity as resiliency strategies is suggested to cope with the demand disruption. Satisfaction demand level is utilized for the agile approach. This research proposes Robust Stochastic Optimization (RSO), including the weighted expected value and maximum CO 2 for NZRACLSCND. This study locates and determines the flow of CLSC in the home appliance industry by considering NZRA, robustness, and risk against demand disruption. CO 2 emission using the NZRA concept is 233.33% less than without considering NZRA concepts. In addition, the conservative coefficient, agile coefficient, decreased CO 2 coefficient, and the model scale are analyzed. The results show that when the conservative coefficient increases, the risks of CO 2 emission increase. In addition, when the agile coefficient increases, as a result, CO 2 emission increases. Finally, when the decreased CO 2 coefficient and the model scale increase, we can see that CO 2 emission and cost are increased.